Graft patency and progression of coronary artery disease after CABG assessed by angiography-derived fractional flow reserve. (1st October 2020) - Gigante, Carlo; Mizukami, Takuya; Sonck, Jeroen; Nagumo, Sakura; Tanzilli, Alessandra; Bartunek, Jozef; Vanderheyden, Marc; Wyffels, Eric; Barbato, Emanuele; Pompilio, Giulio; Mushtaq, Saima; Bartorelli, Antonio; et al.
Abstract: Background: Graft occlusion after coronary artery bypass graft surgery (CABG) has been associated with native coronary artery competitive flow. Objectives: The present study aims to characterize the functional progression of coronary artery disease (CAD) in native vessels after CABG, and to assess the relationship between preoperative FFR as derived from angiography and graft occlusion. Methods: Multicenter study of consecutive patients undergoing CABG between 2013 and 2018, in whom a follow-up angiogram had been performed. Serial vessel-fractional flow reserve (vFFR) analyses were obtained in each major native coronary vessel before and after CABG, excluding post-anastomotic segments and graft conduits. Results: In 73 patients, serial angiograms were suitable for vFFR analysis, including 118 grafted (86 arterial and 32 saphenous grafts) and 64 non-grafted vessels. The median time between CABG and follow-up angiography was 2.4 years [IQR 1.5, 3.3]. Functional CAD progression, by means of decline in vFFR, was observed in grafted but not in non-grafted vessels (delta vFFR in grafted vessels 0.10 [IQR 0.05, 0.18] vs. 0.01 [IQR -0.01, 0.03], in non-grafted vessels, p < 0.001). Preoperative vFFR predicted graft occlusion (AUC: 0.66, 95% CI 0.52 to 0.80, p = 0.031). Conclusions: In patients undergoing CABG, preoperative vFFR derived from conventional angiograms without use of pressure wire was able to predict graft occlusion. Graft occlusion was more frequent in vessels with high vFFR values. Grafted native coronary vessels exhibited accelerated functional CAD progression, whereas in non-grafted native coronaries the functional status remained unchanged. Highlights: In patients undergoing CABG, preoperative non-significant angiography-derived FFR (>0.80) predicted graft occlusion. Grafted native coronary vessels exhibited accelerated functional CAD progression In non-grafted native coronaries the functional status remained unchanged during a median follow-up of 2.4 years.